1986
DOI: 10.1111/j.1432-1033.1986.tb09406.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of adenovirus DNA replication in vitro by autoimmune sera

Abstract: Sera from patients suffering from autoimmune diseases were analyzed for the presence of antibodies that inhibit adenovirus DNA replication in vitro. DNA replication was studied in a reconstituted system containing purified viral proteins (DNA binding protein, DNA polymerase and the precursor to the terminal protein) and a crude nuclear extract from HeLa cells. About half the autoimmune sera analyzed inhibited DNA replication by more than 50% while only 2 out of 31 control sera showed strong inhibition. The inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…In addition Pruijn et al [15] have reported that sera from patients suffering from autoimmune diseases can inhibit adenovirus DNA replication, suggesting a similar phenomenon. The similarities between viral proteins and myelin proteolipid may represent yet another case.…”
Section: Resultsmentioning
confidence: 90%
“…In addition Pruijn et al [15] have reported that sera from patients suffering from autoimmune diseases can inhibit adenovirus DNA replication, suggesting a similar phenomenon. The similarities between viral proteins and myelin proteolipid may represent yet another case.…”
Section: Resultsmentioning
confidence: 90%
“…We used an in vitro reconstituted replication assay to test whether vNFl and vNFlBD retain the functional properties of NFl purified from HeLa cells (Pruijn et al, 1986). 1, 5, 9, 13), 0.1 Id (lanes 2, 6, 10), 0.3 I1 (lanes 3, 7, 11, 14) and 1 Id (lanes 4, 8, 12, 15).…”
Section: Recombinant Vnf1 and Vnf1bd Stimulate Adenovirus Dna Replicamentioning
confidence: 99%
“…Mattaj and G.Tebb (pXLU2.5, containing a X laevis U2 snRNA gene and flanking sequences) (Mattaj et al, 1985 DEAE-cellulose and phosphocellulose chromatography as described (Pruijn et al, 1986a). During the purification procedure the NFE activity was monitored by the stimu- (Pruijn et al, 1986b). The reaction conditions for in vitro replication of Ad2 and Ad4 DNA were as described before (Pruijn et al, 1986a).…”
Section: The Different Affinity Of Nflli For Its Binding Sites In Ad2mentioning
confidence: 99%